2011
DOI: 10.1037/a0022580
|View full text |Cite
|
Sign up to set email alerts
|

The prospective course of postconcussion syndrome: The role of mild traumatic brain injury.

Abstract: The data suggest the phenomenon of PCS in trauma patients does not show an association with mTBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
201
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 263 publications
(215 citation statements)
references
References 77 publications
9
201
3
2
Order By: Relevance
“…The nature and extent of this symptom complex is similar in other patient populations such as those with chronic pain syndromes (14) or following traumas not involving the brain (e.g. after orthopaedic injuries) (6,13). Moreover, healthy controls report post-concussion like symptoms such as cognitive problems, fatigue and headache.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…The nature and extent of this symptom complex is similar in other patient populations such as those with chronic pain syndromes (14) or following traumas not involving the brain (e.g. after orthopaedic injuries) (6,13). Moreover, healthy controls report post-concussion like symptoms such as cognitive problems, fatigue and headache.…”
mentioning
confidence: 59%
“…However, these parameters or other biological explanations do not predict the persistence of symptoms or occurrence of post-concussion syndrome (11). Although its name suggests that this symptom complex is specifically seen after concussion, post-concussion syndrome seems not specifically related to mTBI (6,12,13). The nature and extent of this symptom complex is similar in other patient populations such as those with chronic pain syndromes (14) or following traumas not involving the brain (e.g.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…15 The investigators found similar rates of PCS at 3 months post-injury within both groups. Furthermore, pre-injury depression or anxiety and acute post-traumatic stress predicted PCS regardless of mTBI.…”
mentioning
confidence: 86%
“…Post-concussion symptoms are nonspecific in nature and can be found across a variety of clinical populations. They can be influenced by post-traumatic stress, 14 preinjury depression or anxiety, 15 risk factors such as premorbid cognitive problems, substance use, and psychosocial stressors, The use of trauma patients with orthopedic injuries as a comparison group allows investigators to control for confounding factors that influence the clinical presentation of patients with mTBI, such as post-trauma stress and pre-injury risk factors including behavioral factors that predispose a person to injury. A recent study examined cognitive performance in 123 patients with mTBI and 100 age and sex matched orthopedically injured controls (OC) at presentation to the ED 1 week, and 3 months post-injury.…”
mentioning
confidence: 99%